Evidence of effects of herbivory on Arctic vegetation: a systematic map protocol - Soininen, Eeva M; Barrio, I.; Jepsen, Jane Uhd; Ehrich, Dorothee; Ravolainen, Virve T.; Speed, James David Mervyn (Environmental Evidence, 2018)
Source at https://doi.org/10.1186/s13750-018-0135-1 . Version of record, licensed CC BY-NC-ND 4.0. Background : Along with climate change, herbivory is considered a main driver of ecosystem change in terrestrial Arctic environments. Understanding how herbivory influences the resilience of Arctic ecosystems to ongoing environmental changes is essential to inform policy and guide sustainable management practices. However, many studies indicate that the effects of herbivores on plants and ecosystem functioning depend on the abiotic and biotic conditions where the interaction takes place, i.e. the ecological context. Yet, the range of ecological contexts in which herbivory has been studied in the Arctic has not been systematically assessed. A lack of such evaluation prevents understanding the robustness and generalizability of our knowledge of Arctic herbivore effects on vegetation and ecosystems. The main objective of our systematic map is to identify the ecological contexts where herbivory is studied in the Arctic. Hence, this systematic map will enable us to assess our ability to make generalizable and robust conclusions regarding the impacts of Arctic herbivory. Methods : We will search academic and grey literature using databases, search engines and specialist websites, and select studies addressing the response of the plant(s) to herbivory, deemed relevant in terms of (i) population (terrestrial Arctic plants and plant communities), (ii) exposure (herbivory, including disturbance and fertilization effects of herbivores), and (iii) modifier (ecological context being in the terrestrial Arctic including forest-tundra). We will synthesize the results using systematic mapping approaches.